2023
DOI: 10.3389/feart.2023.1183329
|View full text |Cite
|
Sign up to set email alerts
|

Structural architecture and late Cenozoic tectonic evolution of the Ulsan Fault Zone, SE Korea: New insights from integration of geological and geophysical data

Abstract: Integration of geological and geophysical data is essential to elucidate the configuration and geometry of surface and subsurface structures, as well as their long-term evolution. The NNW–SSE-striking incised valley and parallel mountain range in the southeastern margin of the Korean Peninsula, extending 50 km from Gyeongju to Ulsan cities, are together regarded as one of the most prominent geographical features in South Korea. This paper presents an investigation into the structural architecture and deformati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 65 publications
(82 reference statements)
0
4
0
Order By: Relevance
“…However, subsequent studies have suggested that the UFZ is located either in and around the incised valley, or that it lies along the mountain front to the east of the incised valley, or possibly in both locations (Okada et al, 1998;Ryoo et al, 2002;Choi, 2003;Choi et al, 2006;Ryoo, 2009;Kee et al, 2019;Naik et al, 2022). A recent study attempted to comprehensively re-interpret previous studies along with adding new field observations and geophysical data to propose a new definition of the UFZ (Cheon et al, 2023). This definition includes some strands of exposed faults along the 100 mountain front and several strands of buried faults near the centre of the incised valley (Fig.…”
Section: Study Area 90mentioning
confidence: 99%
See 3 more Smart Citations
“…However, subsequent studies have suggested that the UFZ is located either in and around the incised valley, or that it lies along the mountain front to the east of the incised valley, or possibly in both locations (Okada et al, 1998;Ryoo et al, 2002;Choi, 2003;Choi et al, 2006;Ryoo, 2009;Kee et al, 2019;Naik et al, 2022). A recent study attempted to comprehensively re-interpret previous studies along with adding new field observations and geophysical data to propose a new definition of the UFZ (Cheon et al, 2023). This definition includes some strands of exposed faults along the 100 mountain front and several strands of buried faults near the centre of the incised valley (Fig.…”
Section: Study Area 90mentioning
confidence: 99%
“…A recent (Cheon et al, 2023) also divided the incised valley containing the UFZ on the basis of: (1) differences in faulthosting rocks, and (2) width of the deformation zone. These authors divided the UFZ into only two northern and southern segments 655 at the boundary between our segments 3 and 4.…”
Section: Cases A1 and A2mentioning
confidence: 99%
See 2 more Smart Citations